(untitled) (CAHIERS MAGELLANES-NS, 2024)
Stainless Steel 202 is a popular material in various industrial applications due to its excellent corrosion resistance, high strength, and cost-effectiveness compared to other stainless-steel grades like 304 or 316. So, the current experimental study is to investigate the Gas Tungsten Arc Welding (GTAW;) process for welding stainless steel 202 (SS202) using an SS310 filler rod, with the goal of achieving the best mechanical properties and minimal heat-affected zone (HAZ). The welding parameters considered are the main current, start current, end current, and pulse (Hz), and the Taguchi orthogonal array L9 was employed to systematically investigate their impact on weld quality. The analysis of mechanical properties and microstructure provides a clear understanding of the relationship between the chosen welding parameters and the weld performance. The final result should yield a combination of settings that offers the best compromise between weld strength, minimized HAZ, and improved overall weld quality.